Radical information literacy : reclaiming the political heart of the IL movement - Whitworth, Andrew (Chandos information professional series., 2014)
This text presents a theory of Digital, Media and Information Literacy (DMIL) that synthesizes key theorists' diverse perspectives and positions on DMIL and information behavior, both in the classroom and the workplace, and within the informal learning processes of society. It includes the field of 'community informatics'.